Adherence to the Mediterranean Diet Improves Fatty Acids Profile in Pediatric Patients with Idiopathic Nephrotic Syndrome - Turolo Stefano (MDPI AG, 2021)
The fatty acid profiles of patients with idiopathic nephrotic syndrome (INS) are different from that of healthy controls, even during remission, revealing an increase of the pro-inflammatory omega 6 series. It is still unknown whether the concomitance of nephrotic syndrome affects the potential positive effects of the Mediterranean diet on the levels of omega 3 and 6 fatty acids. We performed a cross-sectional study to evaluate the association between the adherence to the Mediterranean diet and fatty acid profile in 54 children with INS. The dietary habits were assessed through the validated Kidmed questionnaire. Patients with higher adherence had lower levels of linoleic acid and total omega-6. Moreover, a negative correlation between proteinuria and the anti-inflammatory omega-3 series was found. In conclusion, patients with INS with proteinuria and low adherence to the Mediterranean diet have an imbalance in the omega-6/omega-3 ratio that may benefit from following the Mediterranean diet.